EFFECTS OF ORAL FLUIDS AND INTRAVENOUS FLUIDS IN THE IMPROVEMENT OF AMNIOTIC FLUID INDEX DURING THIRD TRIMESTER OF PREGNANCY - Malik, Mehwish; Irshaad, Samina; Bokhari, Nadia Ahmed; Qazi, Wardah Ajaz; Raza, Asia; Bashir, Kanwal (Pakistan Armed Forces Medical Journal, 2021)
Objective: To assess the effects of oral fluids and intravenous fluids in terms of frequency of improving Amniotic Fluid Index during third trimester of pregnancy having oligohydramnios.Study Design: Comparative prospective survey.Place and Duration of Study: Obstetrics and Gynaecological Department of Fauji Foundation HospitalRawalpindi, from Apr 2018 to Oct 2018.Methodology: A total of 100 patients with singleton pregnancy (50 in each group) at gestational age of 28-37weeks and AFI of 5cm or less than 5cm were included. Non probability consecutive sampling technique wasused. Ethics approval from hospital ethical committee and research board was taken. Patients were randomizedinto 2 groups (50 patients each) by lottery method. Group A was instructed to drink 2 liters of water per day fora time period of seven days and patients in group B was given 2 liters of 5% D/W which was in addition to theirnormal fluids intake. Amniotic fluid index was measured pre hydration and post hydration in both groups. Datawas analyzed using SPSS-21.Results: Mean age of the patients was 33.62 ± 5.45 years and 34.70 ± 4.76 years for groups A and B respectively.In group A and group B mean gestational age was 34.28 ± 1.85 weeks vs 34.32 ± 1.82 weeks. In group A, 44 (88%)..............